THE PERCEPTION OF SUFISM IN THE POEMS OF MUSTAFA INCEDIL, ONE OF HATAY'S MASTER LOVERS - Hüseyin Kürşat TÜRKAN (Fırat University, 2021)
Sufism, which can be defined as turning towards God by giving up all worldly enthusiasm and desires, has become a common understanding among Turks who have entered the Islamic religion en masse since the tenth century. The similarity between the “kam” type in the pre-Islamic period and the “guardian” type in the Islamic period played an active role in the Turks easy adoption of Islam. Sufism became widespread as a result of the members of Sufism traveling across Anatolia, “Yesevism, Bektashism, Kadirism, etc.” It has been instrumental in the formation of sects and lodges based on differences of opinion such as. Although there are differences of opinion in these sects, the main goal is the same. The aim of the representatives to the nephew, who are trying to reveal a literary understanding based on the love of God and the prophet in different mediums by nourishing from the same roots, is to try to perform the perception and understanding of Sufism in a manner that the public can understand, in a way that the people can understand. Thus, under the roof to be named "Religious Sufi Literature", the principles and procedures of Islam started to be conveyed by the minstrels, who had a rich tradition and past, through the forms and forms of national poetry. These representatives, as they grew up with a master-apprentice relationship, are accustomed to writing on non-religious subjects and have also begun to write poems on religious subjects. The new acquisition of the tradition has been passed down from generation to generation and carried over to the present day through new apprentices. Within the tradition of minstrelsy, many minstrels have been raised from the first representatives to the present day. Among the aforementioned lovers, there are also those who play saz and utter poetry, as well as those who cannot play saz and sing poems. In this context, playing the saz has a special place and importance in tradition as well as making words. Mustafa İncedil from Hatay is one of the lovers who knows how to play saz in addition to the irtical feature in the execution environment. It was determined that Mustafa İncedil, one of the lovers of Hatay region, wrote poems on religious subjects, being influenced by the aforementioned sects and lodges. In the study, after giving brief information about the life of Asaq Incedil from Hatay and his perception of tsavvuf, some of his poems with Sufism content will be examined under certain headings in order to determine the perception of Sufism in the subject.